Mitochondria as new therapeutic targets for eradicating cancer stem cells: Quantitative proteomics and functional validation via MCT1/2 inhibition - Lamb, Rebecca; Harrison, Hannah; Hulit, James; Smith, Duncan L; Lisanti, Michael P; Sotgia, Federica (Oncotarget, 2014)
Here, we used quantitative proteomics analysis to identify novel therapeutic targets in cancer stem cells and/or progenitor cells. For this purpose, mammospheres from two ER-positive breast cancer cell lines (MCF7 and T47D) were grown in suspension using low-attachment plates and directly compared to attached monolayer cells grown in parallel. This allowed us to identify a subset of proteins that were selectively over-expressed in mammospheres, relative to epithelial monolayers. We focused on mitochondrial proteins, as they appeared to be highly upregulated in both MCF7 and T47D mammospheres. Key mitochondrial-related enzymes involved in beta-oxidation and ketone metabolism were significantly upregulated in mammospheres, as well as proteins involved in mitochondrial biogenesis, and specific protein inhibitors of autophagy/mitophagy. Overall, we identified >40 "metabolic targets" that were commonly upregulated in both MCF7 and T47D mammospheres. Most of these "metabolic targets" were also transcriptionally upregulated in human breast cancer cells in vivo, validating their clinical relevance. Based on this analysis, we propose that increased mitochondrial biogenesis and decreased mitochondrial degradation could provide a novel mechanism for the accumulation of mitochondrial mass in cancer stem cells. To functionally validate our observations, we utilized a specific MCT1/2 inhibitor (AR-C155858), which blocks the cellular uptake of two types of mitochondrial fuels, namely ketone bodies and L-lactate. Our results indicate that inhibition of MCT1/2 function effectively reduces mammosphere formation, with an IC-50 of ~1 µM, in both ER-positive and ER-negative breast cancer cell lines. Very similar results were obtained with oligomycin A, an inhibitor of the mitochondrial ATP synthase. Thus, the proliferative clonal expansion of cancer stem cells appears to require oxidative mitochondrial metabolism, related to the re-use of monocarboxylic acids, such as ketones or L-lactate. Our findings have important clinical implications for exploiting mitochondrial metabolism to eradicate cancer stem cells and to prevent recurrence, metastasis and drug resistance in cancer patients. Importantly, a related MCT1/2 inhibitor (AZD3965) is currently in phase I clinical trials in patients with advanced cancers: http://clinicaltrials.gov/show/NCT01791595.